(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The purpose of this essay is to reflect on the notion of right to privacy in India and toconcentrate on different aspects of it. In India’s Constitution, the right to privacy has been seen as anunarticulated basic right. Changes in the country’s technological, political, social, and economiclandscape demand the acknowledgment of new rights. The law evolves in response to societaldevelopments. One such right that has emerged as a result of expanding the scope of Article 21 is theright to privacy. Despite the fact that the Supreme Court has declared this right to be a basic right underArticle 21 of the Constitution and various other sections of the Constitution read in conjunction with theDirective Principles of State Policy, it is not absolute. Because it is an integral aspect of life and personalliberty, the rising infringement of this right by the state on spurious grounds has prompted the Indianjudiciary to take a proactive role in safeguarding it.This article has examined many concerns and challenges in the technological age in terms of privacyregulations, with a focus on UIDAI, Data Protection in the Telecom Sector, Cyber Privacy, and Real-TimeTracking, among other topics. The report finishes by outlining the activities and actions that may beperformed to address the aforementioned issues. It will focus on the areas where the government mustpay the greatest attention in order to protect individual rights.